Lung cancer screening by low-dose CT scan in France: final results of the DEP KP80 study after three roundsResearch in context - Olivier Leleu; Nicolas Storme; Damien Basille; Marianne Auquier; Valerie Petigny; Pascal Berna; Alexia Letierce; Sebastien Couraud; Julie de Bermont; Bernard Milleron; Vincent Jounieaux (EBioMedicine)
Summary: Background: In prior randomised controlled trials, lung cancer screening using low-dose computed tomography (LDCT) has been shown to reduce lung cancer mortality and overall mortality. Despite these results, organised screening in France remains a challenge.This study assessed the feasibility and efficacy of lung cancer screening within a real-life context in a French administrative territory. Methods: DEP KP80 was a single-arm prospective study. Participants aged between 55 and 74 years, smokers or former smokers of ≥30 pack-years, were recruited. An annual LDCT scan was scheduled and three rounds were performed. Subjects were selected by general practitioners or pulmonologists, who checked the inclusion criteria and prescribed the CT scan. Findings: Between March 2016 and February 2020, 1254 participants were enrolled. Overall, 945 (75.4%) participants underwent baseline LDCT (T0), 376 (42.8%) completed the first round (T1) and 270 (31%) the second (T2) one. Forty-two lung cancers were diagnosed, 30 cancers (71.4%) were stage I or II and 34 cancers (80.9%) were treated surgically. In this study, the overall positive predictive value for a positive screening was 48% (95% CI 37–59) and the negative predictive value 100% (95% CI 100–100). Interpretation: This study demonstrated the feasibility and efficacy of lung cancer screening in a real-life context with most lung cancers diagnosed at an early stage and surgically removed. Our results also highlighted the importance of participation in each round, underlining the fact that optimising organisation is a major goal. Funding: Agence Régionale de Santé de Picardie, La Ligue contre le cancer, le Conseil Départemental de la Somme, and AstraZeneca.